Kajian Ekonomi Pengembangan Ikan Asap di Kampung Melayu Kota Semarang - Ida Rahayu Widowati; Theresia Dwi Hastuti; Robert Rianto Widjaja (JEMAP, 2026)
Smoked fish is a favorite side dish in Semarang. This smoked fish business will be tested and developed in Kampung Melayu, albeit on a small industrial scale. Smoked fish is a household-based economic activity. This economic study of smoked fish development in Kampung Melayu aims to improve the social, economic, and culinary tourism sectors. Current challenges in the smoked fish development area in Kampung Melayu include the need for adequate land for smoked fish production, marketing, and creating a comfortable environment for culinary tourism to increase community income. This study uses a descriptive qualitative method. The main objective of this study is to provide a pleasant and comfortable environment for smoked fish development in Kampung Melayu to improve the community's economy and culinary tourism. This study provides insight into the integration of economic components into environmental management systems to achieve sustainable development